Evaluation of the Implementation of Law No. 17 of 2008 Concerning Shipping in Relation to National Maritime Security: Evaluasi Implementasi Undang-Undang No. 17 Tahun 2008 Tentang Pelayaran Terhadap Keamanan Maritim Nasional - Nurhalisa Kasim; Moh. Bayu Saputra; Melki Kadullah; Vira Auliya Juliharto; Nurjannah D. Buhungo (Yayasan Cerdas Pedia Indonesia, 2025)
Evaluation of the implementation of Law No. 17 of 2008 on shipping shows the importance of the role of shipping law in maintaining national maritime security and sovereignty. As a strategic archipelagic country, Indonesia needs a shipping system that is safe, efficient, and in line with international law such as SOLAS 1974, UNCLOS 1982, and SUA Convention 1988. Normatively, this law has provided a strong legal basis for ship safety, water surveillance, and maritime law enforcement. However, its implementation is still constrained by coordination between institutions, limited resources, and weak supervision. The nine-dash line case in the North Natuna Sea shows the urgency of consistently applying shipping laws to protect national sovereignty. Institutional strengthening and inter-agency synergies are needed to improve the effectiveness of the implementation of shipping law and build a resilient and competitive maritime system.